Seven Tlingit totem poles, Howkan, Alaska, ca. 1904 - Nowell, Frank H., 1864-1950
Seven Tlingit totem poles, Howkan, Alaska, ca. 1900-1908. The poles are various shapes and sizes, some painted. Caption on image: Totem poles. Ketchikan. Note from unidentified source: Totem poles, Ketchikan, in graveyard